Análisis del Liderazgo Gerencial y su influencia en el Desempeño Laboral: Caso empresa de fumigación - Carrasco, Roberto; Vega Chica, Mayra (Compendium: Cuadernos de Economía y Administración; Vol. 11 Núm. 1 (2024): Revista Compendium: Cuadernos de Economía y AdministraciónDO - 10.46677/compendium.v11i1.1174, 2024)
The general objective of this project is to analyze the type of managerial leadership and how it influences the performance of the employees of a fumigation company. The present project was made from a mixed approach, so it was necessary to use the quantitative and qualitative method and correlational scope, through this investigation it was possible to determine the relationship between leadership and job performance statistically through the Spearman coefficient method. Surveys were carried out on permanent workers and not eventual fumigation companies with various dimensions, applied to a sample of 43 people, measuring the two main variables, leadership style and job performance. It is concluded that there is a relationship between leadership style and work performance, for this reason several ideas were proposed so that there is an improvement in work performance, since there are proposals for communication and recognition of the best employee of the month, a corporate manual, a recruitment program be proposed with the objective that it is not carried out empirically.